Inovasi Manajemen Peserta Didik pada Sekolah Islam di Era Society 5.0: Integrasi Teknologi Digital, Pengembangan Potensi dan Nilai-Nilai Islam - Afif Hasbi Bustomi; Mudofir; Imam Makruf (LP2M IAIN Sultan Amai Gorontalo, 2026)
The accelerating digital transformation and the emergence of Society 5.0 require Islamic schools to transform student management practices to address increasingly complex educational demands. This study aims to analyze innovations in student management within Islamic schools in Indonesia and to formulate a management model that is relevant to the challenges of Society 5.0. The study employed a qualitative approach using a conceptual paper design through library research. Data were collected from journal articles, books, research reports, and policy documents related to student management, digital transformation, and Islamic education. Data were analyzed using content analysis and thematic synthesis techniques. The findings reveal that the digitalization of student services remains largely focused on administrative functions, student talent development has not been fully data-driven, and the strengthening of Islamic character faces challenges within the digital ecosystem. Furthermore, student management practices tend to operate in a fragmented manner. This study proposes an Integrated Student Management Model consisting of Digital Student Management, Student Talent Development, and Islamic Character Development. The proposed model is expected to serve as a conceptual framework for developing adaptive, holistic, and Islamic character-based student management in the Society 5.0 era.